2008
DOI: 10.1002/mrc.2207
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of 1H → 31P NMR cross‐polarization in bone apatite and its mineral standards

Abstract: Kinetics of NMR cross-polarization (CP) from protons to phosphorus-31 nuclei was studied in the following samples: mineral of whole human bone, apatite prepared from bone, natural brushite, synthetic hydroxyapatite (hydrated and calcined), and synthetic carbonatoapatite of type B with 9 wt% of CO(3) (2-). In order to avoid an effect of magic angle spinning on CP and relaxation, the experiments were carried out on static samples. Parameters of the CP kinetics were discussed for trabecular and cortical bone tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 43 publications
(71 reference statements)
7
39
0
Order By: Relevance
“…This is why in such experiments signal intensity must be compared over a variety of contact times, and not only for its fixed value. Such investigations were carried out considering the phosphorus components and their structure in bone (the graph of intensity vs. contact time is strongly dependent on the material structure) [3639] and bone implants [33] (Fig. 9).…”
Section: Solid-state Nmr (Ssnmr)mentioning
confidence: 99%
“…This is why in such experiments signal intensity must be compared over a variety of contact times, and not only for its fixed value. Such investigations were carried out considering the phosphorus components and their structure in bone (the graph of intensity vs. contact time is strongly dependent on the material structure) [3639] and bone implants [33] (Fig. 9).…”
Section: Solid-state Nmr (Ssnmr)mentioning
confidence: 99%
“…Bone consists of approximately 65% mineral, 25% organic matrix, and 10% water by weight [5]. Electron microscopy studies have revealed that chemically isolated bone minerals have globular morphologies of sizes from 70 to 90 nm, which are aggregates of smaller particles with sizes around 20 nm [6].…”
Section: Introductionmentioning
confidence: 99%
“…The biological apatite nanocrystal consists of a nanocrystalline apatite core enclosed by a 1-2 nm amorphous layer of calcium phosphate that has been postulated to be a precursor of hydroxyapatite formation [4,5,7,8,16,17]. Minerals octacalcium phosphate (Ca 8 (HPO 4 ) 2 (PO4) 4 ·5H 2 O) and brushite (CaHPO 4 ·2H 2 O) have been considered possible compositions of the amorphous layer [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Since CP relies on heteronuclear dipolar couplings between the source and target spins, its efficiency is uniquely dependent on the concentration, distribution and mobility of the nuclei involved. In particular, CP has been widely used to obtain insights about the composition of different calcium phosphate salts and thus distinguish them—for instance, bone apatites from synthetic ones [24,25], or ACP salts from crystalline ones [26]—based on the different percentages of water molecules and hydroxyl groups that characterize each particular calcium phosphate type. In the particular case of crystalline apatites and amorphous calcium phosphate salts, CP efficiency is typically linear for contact times longer than 8 ms in the former case, whereas it reaches a maximum earlier in the latter because there are fewer apatite-structural-hydroxyl groups than water molecules occupying the interstices among the ACP clusters [26].…”
Section: Resultsmentioning
confidence: 99%